Individualised music for people living with dementia and the experiences and perceptions of residential aged care staff: A qualitative study. (5th August 2021) - Gaviola, Minah Amor; Higgins, Isabel; Dilworth, Sophie; Holliday, Elizabeth; Inder, Kerry J.
Abstract: Objective: To explore the experiences and perceptions of staff regarding the use of individualised music for people with dementia living in residential aged care. Methods: A qualitative descriptive methodology was used. Methods included a focus group and face‐to‐face interviews, open‐ended responses to a pre‐post survey and relevant clinical notes about older participants' responses. Qualitative content analysis was used to analyse data. Results: There were four themes: (1) transcendental reminiscing, the calm, the joy and the elation; (2) optimism, excitement and the snowball effect; (3) pitching in for older person, it is not rocket science and the hurdles; and (4) music beyond the intervention. Conclusions: Overall, the individualised music was a generally positive experience. While some older participants reported discomfort with the use of headphones, staff concerns related to care and accessibility of music equipment.